THE INFLUCENCE OF CLOUD TECHOLOGY IN TRANSFORMING ACCOUNTING PRACTICES - ANDRONIE, Maria; IONESCU, Luminita (Annals of Spiru Haret University. Economic Series, 2019)
Cloud is one of the most important developments in information technology in the past decade with significant consequences over the financial reporting for businesses and individuals, as well. It is considered to be indispensable to accountants in the near future and will improve the accuracy of financial information and the business strategy. The most recent developments tend to confirm that cloud computing or cloud technology in accountancy has been transformative in how accountants work on daily basis with their clients and how they communicate the fiscal information to the tax authorities. The aim of this paper is to present some particular aspects of cloud technology in accounting, and how cloud accounting platform could provide an accurate and comprehensive dataset in financial reporting.